Waqf on Environmental Issue: A Systematic Review - Sri Rahayu; Mohammad Iqbal Irfany (International Journal of Waqf, 2022)
The purpose of this research is to identify and map research related to the development of research trends in Waqf and the Environment. The data analyzed are articles published by leading journals from 2006 to 2021. The number of articles analyzed is 30 articles indexed by Scopus. The research methods are descriptive statistical methods and bibliometric analysis. The results of the study show that the number of articles discussing the theme of Waqf and Environment shows an increasing trend starting from 2015. The popular keywords used are waqf, cash waqf, and environment. The most prolific writers are Abdul Majid N.H, Denan Z, and Ismail S, while the country with the m ost popular and the most number of writers in Malaysia. This research provides information for researchers who focus on research in the field of Waqf and Environment.